2008
DOI: 10.1063/1.2989133
|View full text |Cite
|
Sign up to set email alerts
|

Improved electron injection in polymer light-emitting diodes using anionic conjugated polyelectrolyte

Abstract: We report improved performance in polymer light-emitting diodes incorporating conjugated polyelectrolytes as an electron injection layer (EIL). When we introduce water soluble conjugated polymers, poly[9,9′-bis(4-sulfonatobutyl)fluorene-co-alt-1,4-phenylene] (anionic PFP), between the aluminum (Al) cathode and emissive layer, the devices show an increased electroluminescence efficiency with a lowered turn-on voltage. We believe the mobile Na+ ions in the EIL layer directly influences the device efficiency by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…Moreover, solution-processed multilayer devices, which are critical for a better device performance, can be easily realized by depositing different layers with orthogonal solvents. For examples, many types of highly polar pendant groups (such as cationic, 8,14,42,43 anionic, 44,45 zwitterionic 34,46,47 and neutral highly polar pendant groups 14,18,32,[48][49][50][51][52] ) and conjugated main chain building blocks (such as uorene, 8,14,18,34,[42][43][44][45][46][47][48][49][50][51] carbazole, 30,52 triphenylamine, 32,53,54 thiophene 23,27,33 etc.) 3,5,[14][15][16] In polymer light-emitting diodes (PLEDs), WSCPs can greatly enhance the electron injection from high work-function metal cathodes, which in turn leads to the realization of high-efficiency all-printable PLEDs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, solution-processed multilayer devices, which are critical for a better device performance, can be easily realized by depositing different layers with orthogonal solvents. For examples, many types of highly polar pendant groups (such as cationic, 8,14,42,43 anionic, 44,45 zwitterionic 34,46,47 and neutral highly polar pendant groups 14,18,32,[48][49][50][51][52] ) and conjugated main chain building blocks (such as uorene, 8,14,18,34,[42][43][44][45][46][47][48][49][50][51] carbazole, 30,52 triphenylamine, 32,53,54 thiophene 23,27,33 etc.) 3,5,[14][15][16] In polymer light-emitting diodes (PLEDs), WSCPs can greatly enhance the electron injection from high work-function metal cathodes, which in turn leads to the realization of high-efficiency all-printable PLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…17 Aerwards, it was demonstrated that WSCPs also worked well as interlayers in polymer solar cells (PSCs). For example, WSCPs with electron-rich main chains (such as polyuorene, 8,14,18,34,[42][43][44][45][46][47][48][49][50][51] polycarbazole 30,52 and polythiophene 23,27,33 ), which have been previously considered as typical p-type semiconductors, behaved very well as interface modication layers for cathodes in PLEDs and for electroncollecting electrodes in PSCs. [39][40][41] For their versatile applications in optoelectronic devices, many efforts have been paid to the development of new WSCPs interlayer materials.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the HyPLECs exhibit extremely low turn-on, and high luminance efficiency at low operating voltage without matching the work functions between each electrode and active layer. 23,24 The device performances of FTO/ZnO/SY:ILMs blend/Au device with different ILMs content and FTO/ SY:ILMs blend ͑25 wt %͒/Au device are presented in Fig. 2.…”
mentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22] The nominal difference between an LEC and an OLED is that the former contains mobile ions in the active material. [23][24][25][26][27][28][29][30] These ions rearrange during operation, which in turn allows for a range of attractive device properties, including low-voltage operation with thick active layers and stable electrode materials. [31][32][33][34][35][36] However, the further development of LECs is currently hampered by an inadequate understanding of the device operation.…”
mentioning
confidence: 99%